2012
DOI: 10.1021/nl303358p
|View full text |Cite
|
Sign up to set email alerts
|

Direct Optical Imaging of Graphene In Vitro by Nonlinear Femtosecond Laser Spectral Reshaping

Abstract: Nonlinear optical microscopy, based on femtosecond laser spectral reshaping, characterized and imaged graphene samples made from different methods, both on slides and in a biological environment. This technique clearly discriminates between graphene flakes with different numbers of layers and reveals the distinct nonlinear optical properties of reduced graphene oxide as compared to mechanically exfoliated or chemical vapor deposition grown graphene. The nonlinearity makes it applicable to scattering samples (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…Since the discoveries of fullerene C 60 in 1985 1 , carbon nanotubes (CNTs) in 1991 2 , and graphene in 2004 3 , carbon-based nanomaterials (CBNs) have attracted considerable attention in various biomedical fields 4 5 (including those related to gene delivery 6 , optical imaging 7 , and nanotherapeutics) 8 9 10 11 12 because of their excellent mechanical, optical, and electrical properties 13 14 15 . However, growing concerns over pathologies CBNs might effect on human patients have established the study of nanotoxicity as an important element of nanoscience and nanotechnology 16 17 18 19 .…”
mentioning
confidence: 99%
“…Since the discoveries of fullerene C 60 in 1985 1 , carbon nanotubes (CNTs) in 1991 2 , and graphene in 2004 3 , carbon-based nanomaterials (CBNs) have attracted considerable attention in various biomedical fields 4 5 (including those related to gene delivery 6 , optical imaging 7 , and nanotherapeutics) 8 9 10 11 12 because of their excellent mechanical, optical, and electrical properties 13 14 15 . However, growing concerns over pathologies CBNs might effect on human patients have established the study of nanotoxicity as an important element of nanoscience and nanotechnology 16 17 18 19 .…”
mentioning
confidence: 99%
“…Fluorescence quenching microscopy was recently employed to quickly visualize graphene based sheets, where a fluorescent dye was coated on the surface22. A nonlinear optical microscopy method based on self-phase modulation was used for in vitro imaging of graphene, but this contrast is not sensitive to GO23.…”
mentioning
confidence: 99%
“…Peng et al demonstrated that the photoluminescence of the nano‐GO can be tailored through varying the size of the nano‐sheets 139. The application of this technique to cancer cell imaging has already been investigated with different types of cells, gastric cancer cell line (AGS),140 BT549 breast cancer cells line141 and MG‐63 human osteosarcoma cell line135. Photoluminescence of nano‐GO was also investigated along with the potential application on photothermal cancer cell therapy.…”
Section: Key Points Of Nano‐go On Cancer Therapymentioning
confidence: 99%